Gene therapy in preeclampsia: the dawn of a new era - Fengxuan Sun; Maureen Peers de Nieuwburgh; Corinne Hubinont; Frédéric Debiève; Arthur Colson (Taylor & Francis Group, 2024)
Preeclampsia is a severe complication of pregnancy, affecting an estimated 4 million women annually. It is one of the leading causes of maternal and fetal mortality worldwide, and it has life-long consequences. The maternal multisystemic symptoms are driven by poor placentation, which causes syncytiotrophoblastic stress and the release of factors into the maternal bloodstream. Amongst them, the soluble fms-like tyrosine kinase-1 (sFLT-1) triggers extensive endothelial dysfunction by acting as a decoy receptor for the vascular endothelial growth factor (VEGF) and the placental growth factor (PGF). Current interventions aim to mitigate hypertension and seizures, but the only definite treatment remains induced delivery. Thus, there is a pressing need for novel therapies to remedy this situation. Notably, CBP-4888, a siRNA drug delivered subcutaneously to knock down sFLT1 expression in the placenta, has recently obtained Fast Track approval from the Food and Drug Administration (FDA) and is undergoing a phase 1 clinical trial. Such advance highlights a growing interest and significant potential in gene therapy to manage preeclampsia. This review summarizes the advances and prospects of gene therapy in treating placental dysfunction and illustrates crucial challenges and considerations for these emerging treatments.